Governing Europe's marine environment Europeanization of regional seas or regionalization of EU policies? - Gilek, Michael; Kern, Kristine (Corbett Centre for maritime policy studies series, 2016)
Governing Europe's Marine Environment is a coherent up-to-date multidisciplinary analysis of current approaches and challenges to the sustainable governance of Europe's marine environment. Structured in three parts, Part 1 outlines general theoretical ideas about governance, governing, and governability and serves as a starting point for analysing the development of marine governance in Europe from the perspective of different disciplines. Part 2 includes studies of EU marine governance. Part 3 focuses on Europe's regional seas, namely the Baltic Sea, the North Sea, the Black Sea, and the Mediterranean Sea. This book presents a better understanding of the fragmented governance of marine governance in Europe and in particular the tension between the Europeanization of regional seas and the regionalization of EU policies.